2014
DOI: 10.15376/biores.9.3.4212-4225
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of Laccase Production from Pleurotus ostreatus PVCRSP-7 by altering the Nutritional Conditions using Response Surface Methodology

Abstract: Submerged culture conditions for laccase production by Pleurotus ostreatus were optimized by response surface methodology (RSM). A total of six factors, carbon (glucose), nitrogen sources (urea and peptone), 2,5-xylidine (inducer), wheat bran (lignocellulosic material), and medium pH, were optimized. A total of 50 experiments were conducted, and the obtained data were modeled using a second-order polynomial. The optimized conditions show significant improvement in laccase expression, by approximately 3.5-fold … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…It was reported that in SMF, the Lac produced by Pleurotus sajor‐caju , using pulp wash residue as a substrate and optimized by a statistical tool through the response surface methodology, reached an activity of up to 307 379.91 IU L −1 66 . In another study, Chiranjeevi et al 67 . reported that the Lac produced by Pleurotus ostreatus PVCRSP‐7 using wheat bran as a lignocellulosic inducer was able to increase its activity by 3.5 times (approximately 12 124 IU L −1 ) when compared with production without adding the substrate.…”
Section: Wrf and Their Lmesmentioning
confidence: 96%
“…It was reported that in SMF, the Lac produced by Pleurotus sajor‐caju , using pulp wash residue as a substrate and optimized by a statistical tool through the response surface methodology, reached an activity of up to 307 379.91 IU L −1 66 . In another study, Chiranjeevi et al 67 . reported that the Lac produced by Pleurotus ostreatus PVCRSP‐7 using wheat bran as a lignocellulosic inducer was able to increase its activity by 3.5 times (approximately 12 124 IU L −1 ) when compared with production without adding the substrate.…”
Section: Wrf and Their Lmesmentioning
confidence: 96%
“…Its sturdy timber is coveted for crafting mosaic-styled parquet floors, ornamental veneers, high-end furniture, cabinetry, of T1 is reduced to water. Through this enzyme process, the fungus obtains nutrients for its development [29][30][31][32][33]. Therefore, some studies suggest that laccase inhibitors are small molecules capable of binding to the Cu ions of the TCN, thereby interrupting the internal oxidation process such as sodium azide, some small halides, heavy metals, and ethylenediaminetetraacetic acid (EDTA) [34,35].…”
Section: Introductionmentioning
confidence: 99%